TREATMENT ACCESS FOR DUAL DIAGNOSIS SUBSTANCE USE AND MENTAL HEALTH DISORDERS - Banuelos, Pedro (2021)
In 2018, of 1.3 million Latinx adults in the United States facing concurrent issues with substance use disorders (SUD) and mental health disorders (MHD) 93% remained untreated for either diagnosis. This is concerning since Substance Abuse and Mental Health Services Administration (SAMHSA) data reveals that this population is at greater risk for suicidal thoughts, plans, and attempts. They also face structural barriers such as employment, housing, legal involvement, and insurability that further impede access to treatment. This study’s purpose was to examine barriers to accessing treatment for Latinx populations confronting co-occurring SUDs and MHDs. This study used a qualitative design and data were collected from telephone or zoom interviews with five Latinxs who identified themselves as dually diagnosed (DD) within the Inland Empire of Southern California. This study found that participants reported stigma from the community and cultural forces as a major barrier to treatment. The study revealed that participants viewed structural factors such as being uninsured, being incarcerated, having transportation difficulties, and having work scheduling difficulties as barriers to treatment. This study also indicated difficulties in diagnosing a DD, which often led to an inability to consider how one diagnosis might impact another and ultimately delayed actions to treat a DD. It is recommended that social workers ensure understanding of unique DD experiences so they can proactively assess for substance use in early adolescence. To address structural barriers, this study recommends universal access to medical coverage for all individuals, which ultimately foster advanced preventative interventions for DD individuals